Is tissue still the issue? Lobectomy for suspicious lung nodules without confirmation of malignancy. Issue 5 (23rd February 2018) - Kaaki, Suha; Kidane, Biniam; Srinathan, Sadeesh; Tan, Lawrence; Buduhan, Gordon
Abstract : Background: Histologic confirmation of malignancy has been indicated for a suspicious lung nodule prior to resection. The purpose of this study was to determine whether or not foregoing routine tissue biopsy increased the incidence of lobectomy for benign lesions. Methods: Retrospective cohort of 256 patients who underwent thoracoscopic or open lobectomy for a confirmed or suspected pulmonary malignancy, with or without tissue diagnosis. Clinical, radiographic, and pathologic data were compared. Results: Among 256 patients, 127 had attempted biopsy (group A) and 129 had no biopsy procedure (group B). There was no significant difference in the incidence of benign resections between the groups (Group A = 4 (3.2%) benign pathology vs group B = 9 (7.0%; P = 0.16). Group B had significantly lower operative time (127.1 vs 112.3 minutes; P = 0.004) and intraoperative complications (23 vs 37 patients; P = 0.03). There was a trend toward longer hospital stay and surgical waiting time in group A (6.6 vs 5.2 days, P = 0.24; 92.4 vs 66.2 days; P = 0.14, respectively). Conclusion: Foregoing biopsies and proceeding to lobectomy in selected patients with suspicious lung nodules is safe, did not increase the incidence of resected benign pathology, and may decrease surgical wait time. Patients should be carefully evaluated and counseled.